Buckling analyses of cold-formed steel Sigma sections in purlin-sheeting systems subjected to uniformly distributed uplift loading. (December 2021) - Ren, Chong; Liu, Xiaowei; He, Wenfu; Dai, Liusi
Abstract: The buckling behaviour of cold-formed steel (CFS) Sigma sections in purlin-sheeting systems is investigated by Finite Element Analysis (FEA) in this paper. A total of 434 specimens with different web heights, thicknesses and lengths are simulated. The comparison of the longitudinal stress distributions obtained from the EN1993-1–3 and FEA is presented. The moment capacities and load–displacement curves of Sigma sections are predicted by FEA. The significant influence of the distortional-lateral torsional buckling interaction on the performance of Sigma purlins is illustrated. The modified Direct Strength Method (DSM) formulae are proposed to predict the flexural capacities of partially restrained Sigma sections under uniformly distributed uplift loading (UDUL).